Hardware realization of discrete wavelet transform cauchy Reed Solomon minimal instruction set computer architecture for wireless visual sensor networks - Ong, Jia Jan (2016)
Large amount of image data transmitting across the Wireless Visual Sensor Networks (WVSNs) increases the data transmission rate thus increases the power transmission. This would inevitably decreases the operating lifespan of the sensor nodes and affecting the overall operation of WVSNs. Limiting power consumption to prolong battery lifespan is one of the most important goals in WVSNs. To achieve this goal, this thesis presents a novel low complexity Discrete Wavelet Transform (DWT) Cauchy Reed Solomon (CRS) Minimal Instruction Set Computer (MISC) architecture that performs data compression and data encoding (encryption) in a single architecture. There are four different programme instructions were developed to programme the MISC processor, which are Subtract and Branch if Negative (SBN), Galois Field Multiplier (GF MULT), XOR and 11TO8 instructions. With the use of these programme instructions, the developed DWT CRS MISC were programmed to perform DWT image compression to reduce the image size and then encode the DWT coefficients with CRS code to ensure data security and reliability. Both compression and CRS encoding were performed by a single architecture rather than in two separate modules which require a lot of hardware resources (logic slices). By reducing the number of logic slices, the power consumption can be subsequently reduced. Results show that the proposed new DWT CRS MISC architecture implementation requires 142 Slices (Xilinx Virtex-II), 129 slices (Xilinx Spartan-3E), 144 Slices (Xilinx Spartan-3L) and 66 Slices (Xilinx Spartan-6). The developed DWT CRS MISC architecture has lower hardware complexity as compared to other existing systems, such as Crypto-Processor in Xilinx Spartan-6 (4828 Slices), Low-Density Parity-Check in Xilinx Virtex-II (870 slices) and ECBC in Xilinx Spartan-3E (1691 Slices). With the use of RC10 development board, the developed DWT CRS MISC architecture can be implemented onto the Xilinx Spartan-3L FPGA to simulate an actual visual sensor node. This is to verify the feasibility of developing a joint compression, encryption and error correction processing framework in WVSNs.